DAMPAK PARTISIPASI AKADEMIK TERHADAP PERILAKU ANTISOSIAL DAN PRESTASI AKADEMIK PENDIDIKAN IPS UNIVERSITAS TANJUNGPURA - Ramadhani, Diajeng; Syahrudin, Husni; Karolina, Venny (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2025)
This research aims to determine the relationship between academic participation of students in the Social Sciences Education Study Program FKIP Tanjungpura University with antisocial behavior and academic achievement. The research method used in this research is a quantitative approach in the form of correlation. The sample for this research consisted of 83 students of the Social Sciences Education Study Program Class of 2021, 2022 and 2023 with a sampling technique using simple random sampling. Data collection in this research used a questionnaire. Data analysis techniques use descriptive and inferential statistics. The results of the research show that (1) the academic participation of students in the Social Sciences Education Study Program at Tanjungpura University is at the medium category level, namely with an average of 72% (N=59), (2) the antisocial behavior of students at the Social Sciences Education Study Program at Tanjungpura University is at the level of medium category, namely with an average of 64.6% (N=53), (3) there is a relationship between academic participation and antisocial behavior at a moderate level of relationship with a significance value (2-tailed) of 0.000 (sig < 0.05), (4) there is a significant relationship between academic participation and academic achievement with a significance value (2-tailed) of 0.000 (sig < 0.05)